Gambaran Pelaksanaan Posyandu Balita Pada Masa Pandemik di Desa Kasri Kabupaten Malang - Sulistiyah Sulistiyah; Nila Widya Keswara (Journal of Islamic Medicine, 2023)
Background: The Ministry of Health stated that Posyandu had a very important role  during the pandemic to bring basic health services closer to the community and empower mothers in improving the health quality of children and families. The Posyandu in Kasri village has experienced visitor decline, this situation requires strong support from various parties, both moral, material and financial support. In addition, cooperation is needed so that the posyandu can continue to run during the pandemic. Objective: the purpose of this study was to  analyze the portrait of the implementation of Posyandu during the pandemic in Kasri Village, Malang Regency. Methods: This research is a qualitative research with a case study approach (case study). Results: The implementation of the Posyandu for toddlers in Kasri Village during the pandemic is still being carried out. Due to the high concern for mothers, they start to  reduce contact outside. This condition made mothers neglect the health of their toddlers. Thanks to the hard work of posyandu cadres by making home visits so that the activities of the toddler posyandu can still be carried out by paying attention to health protocols. In real, many cadres encountered several obstacles, one of which was rejected by the community. As a result of this pandemic, it is not only the people who are afraid, but the cadres are also worried. Posyandu success cannot be separated from the hard work of health cadres who voluntarily manage posyandu in their area. Conclusion: Implementation of posyandu with home visits of posyandu cadres has paid attention to health protocols in accordance with service technical instructions during the COVID-19 pandemic. The success of the posyandu cannot be separated from the hard work of posyandu cadres and the community in improving health status during the pandemic